DEVELOPMENT AND ECONOMIC-BIOLOGICAL CHARACTERISTICS SORGHUM-SUDAN HYBRIDS - Е. А. Shishova; N. A. Kovtunova; V. V. Kovtunov; А. Е. Romanyukin (Зерновое хозяйство России, 2019)
Due to a high stooling coefficient and good growing after cutting, sorghum can be used in the green conveyor in the summer between the cutting of annual and perennial grasses, in the fall when the growth of perennial grasses stops. Hybridization of Sudan grass with CMS-lines of various sorghum types (grain and sweet), produces highly heterotic sorghum-Sudan hybrids which exceed the parental forms in green mass productivity by 1.5 times or more. The identification of new sorghum-Sudan hybrids with high heterotic effects on productivity of green mass and dry matter with their future introduction into production is an important direction of sorghum breeding. The purpose of this work is to identify the main stages of the development of sorghum-Sudanese hybrids and to estimate indicators of their productivity and quality. The CMS lines of grain and sweet sorghum, highly productive varieties of Sudanese grass and new sorghum-Sudan hybrids are the objects of the study. The initial stage is the selection of parental forms. Highly productive and permanent varieties are of great necessity as pollinators. In our studies, these are the varieties “Svetloplenchataya 1”, “Chernoplenchataya 11” and “Chernoplenchataya 10” with 33–42 t/ha of green mass for 2 cuttings. Due to the more powerful plant development the new sorghum-Sudanese hybrids produce 52–77 t/ha of green mass for 2 cuttings. Genuine heterosis is 22.6–102.6%. During the study there have been identified the hybrids “APV-1115 x Svetloplenchataya 1” and “Zersta 38 x Chernoplenchataya 11”, that combine the maximum values of the productivity of green mass and dry matter.